Development of a multimedia courseware as a teaching aid for children with dyslexia - Zakaria, Mohd Hafiz; Techanamurthy, Umawathy; Devaraju, Anusuriya (2006)
Dyslexia is a language based learning disability resulting in people experiencing difficulties in reading, spelling, writing and speaking. These problems are sometimes compounded by short term memory difficulties, a lack of organisational skills and time management issues which all have an impact on learning. This paper focuses on the planning, analysis and design of an e-learning courseware to teach dyslexics to read using the ‘picture thinking’ model. The development of this e-learning courseware involves transforming the traditional content of printed books from passive prints and illustrations into interactive multimedia content. The interactive multimedia content will focus on clear presentation of materials, good navigational assistance and a variety of multimedia options to tap into visual, auditory and kinaesthetic skills to support dyslexics. The targeted users will be children with dyslexia and pre-schoolers aged 5 to 7 learning to read Bahasa Melayu. A successful implementation of this courseware will be useful to the dyslexic learners as it will use picture thinking model and multisensory approach to the best of their ability instead of approaching them with the same teaching approaches used to teach their non- dyslexic counterparts.